2010
DOI: 10.1007/s13206-010-4401-8
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors that affect Streptococcus mutans biofilm formation in a microfluidic device mimicking teeth

Abstract: Streptococcus mutans is the primary etiological agent responsible for dental caries. Microfluidic devices have been used to provide a level of control over bacterial microenvironments under laminar flow conditions. In this study, we used a microfluidic device packed with glass beads to simulate the interproximal space, which is the space between the teeth. In the device, the effects of environmental factors, such as sucrose and metal ions, on S. mutans attachment and biofilm formation were quantitatively measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…As a result, only a very limited number of studies have shown heterogeneous metal distributions in biofilms (McCall and Fierke, 2000;Ueshima et al, 2008;Wuertz et al, 2000). So far only one ferric chemosensor has been reported for imaging ferric iron distribution in oral biofilms by CLSM using microfluidic devices (Shumi et al, 2010). Although various metal fluorescent probes and their applications have been summarized in a recent review (Carter et al, 2014), most of the probes have been developed for detecting intracellular metal concentrations.In an earlier study we have developed guideline (Hao et al, 2013) for selecting probes for environmental applications.…”
Section: Optimization Of the Clsm Approachmentioning
confidence: 99%
“…As a result, only a very limited number of studies have shown heterogeneous metal distributions in biofilms (McCall and Fierke, 2000;Ueshima et al, 2008;Wuertz et al, 2000). So far only one ferric chemosensor has been reported for imaging ferric iron distribution in oral biofilms by CLSM using microfluidic devices (Shumi et al, 2010). Although various metal fluorescent probes and their applications have been summarized in a recent review (Carter et al, 2014), most of the probes have been developed for detecting intracellular metal concentrations.In an earlier study we have developed guideline (Hao et al, 2013) for selecting probes for environmental applications.…”
Section: Optimization Of the Clsm Approachmentioning
confidence: 99%
“…In this research, we were able to confirm the capacity of ORT to form biofilm, as occurred with S. mutans, which was the strain used as the positive control for biofilm formation. It has been described that S. mutans is able to produce biofilm under diverse pH values, as well as under aerobiosis or elevated CO 2 conditions and at different temperatures (Shumi et al, 2010;Nishimura et al, 2012;Welch et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Using a microfluidic device with glass beads, Shumi et al . simulated the interproximal space of teeth [ 84 ]. They quantified the effects of sucrose and metal ions on biofilm formation in the gaps between glass beads.…”
Section: Microfluidic Approachmentioning
confidence: 99%